PENGARUH FIVE ASPECT MEAL MODEL TERHADAP KEPUASAN KONSUMEN PADA KONSUMEN REDBACK SPECIALITY COFFEE SURABAYA - Joseline Ivana Tanuwidjaja Tan; Yoseva Sumaji (Primanomics : Jurnal Ekonomi & Bisnis, 2024)
RedBack Specialty Coffee is a coffee shop that was founded in 2017 with a modern concept located in elite real estate in West Surabaya. Aspects of the room at RedBack feature an attractive design; the cafe boasts indoor and outdoor spaces, each with its own allure. Customer reviews elaborate that RedBack Coffee GF has excellent decor that aligns with its vibes, which relates to the aspect of atmosphere influencing customer satisfaction. The objective of this research is to ascertain the impact of the Five Aspect Meal Model (consisting of the following elements: Room, Meeting, Product, Management Control System, and Atmosphere) on the dependent variable of Customer Satisfaction as it relates to RedBack Specialty Coffee Surabaya patrons. The research procedure employed in this study is quantitative in nature. The present study employs purposive sampling as its method of sampling. The participants for this study comprised 150 individuals who had patronized RedBack Specialty Coffee Surabaya on at least one occasion within the preceding half-year (November 2022-April 2023). This research employs the SPSS software to analyze the data. The findings of this research demonstrate that various elements of Redback Specialty Coffee—room, meeting, product, management control system, and atmosphere—have a substantial and positive impact on customer satisfaction. The findings of this study emphasize the significance of comprehensive dining experiences in augmenting customer contentment and propose ramifications for the management and marketing approaches of coffee shops.